Circadian Regulation of the Biology of Allergic Disease: Clock Disruption Can Promote Allergy - Nakao, Atsuhito (Frontiers in Immunology, 2020)
Allergic diseases such as allergic rhinitis, asthma, atopic dermatitis, and food allergy are characterized by epithelial barrier dysfunction and deregulated immune responses. Components of the circadian clock interact with critical elements of epithelial barrier function and immune responses, and regulate the biological processes on a 24-hour cycle at steady state. This may represent an anticipatory defense response to day-night fluctuation of attack by pathogens in the environment. This review will summarize clock control of epithelial barrier function and immune responses associated with allergic disease and offer novel insights and opportunities into how clock dysfunction impacts allergic disease. Importantly, perturbation of normal clock activity by genetic and environmental disturbances, such as artificial light at night or irregular eating habits, deregulates epithelial barrier function and immune responses. This implies that the circadian clock is strongly linked to the fundamental biology of allergic disease, and that clock disruption can precipitate allergic disease by altering the epithelial barrier and immune functions. Given that contemporary lifestyles often involve chronic circadian disruptions such as shift work, we propose that lifestyle or therapeutic interventions that align the endogenous circadian clock with environmental cycles should be a part of the efforts to prevent or treat allergic disease in modern society.